2013
DOI: 10.1002/prca.201200048
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics of archival triple‐negative breast cancer samples

Abstract: Our results open up new avenues for the use of proteomics technologies in clinically relevant studies using archival samples. Shotgun LC-MS/MS studies could serve to discover new biomarkers and may provide clues to the genesis of TNBC and underlying molecular alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 56 publications
(72 reference statements)
2
28
0
Order By: Relevance
“…Specifically, the DT workflow entails an initial tissue homogenization, which can be performed using different buffers, such as the commercial Liquid Tissue [16], as well as mixtures of ammonium bicarbonate (ABC) and acetonitrile (ACN) [17,18] or ABC and trifluoroethanol [19,20], followed by direct trypsin digestion of the tissue homogenate. The ISD workflow is instead based on a preliminary protein extraction step, comprising tissue lysis in a detergent-based buffer (usually containing SDS) and collection of soluble proteins after centrifugation, succeeded by detergent depletion (by means of dilution with ABC [21,22], dialysis [23], spin columns [24] or protein precipitation with various protocols [25-28]) and in solution digestion of the protein extract. The FASP protocol, applied with remarkable results to FFPE samples by Wiśniewski and colleagues [29-32] and recently employed with modifications by other research groups [33,34], shares the initial protein extraction step with the ISD workflow but differs in that detergent removal and protein digestion are both performed on a molecular weight cut-off centrifugal filter [35,36], instead of in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the DT workflow entails an initial tissue homogenization, which can be performed using different buffers, such as the commercial Liquid Tissue [16], as well as mixtures of ammonium bicarbonate (ABC) and acetonitrile (ACN) [17,18] or ABC and trifluoroethanol [19,20], followed by direct trypsin digestion of the tissue homogenate. The ISD workflow is instead based on a preliminary protein extraction step, comprising tissue lysis in a detergent-based buffer (usually containing SDS) and collection of soluble proteins after centrifugation, succeeded by detergent depletion (by means of dilution with ABC [21,22], dialysis [23], spin columns [24] or protein precipitation with various protocols [25-28]) and in solution digestion of the protein extract. The FASP protocol, applied with remarkable results to FFPE samples by Wiśniewski and colleagues [29-32] and recently employed with modifications by other research groups [33,34], shares the initial protein extraction step with the ISD workflow but differs in that detergent removal and protein digestion are both performed on a molecular weight cut-off centrifugal filter [35,36], instead of in solution.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that our workflow is high reproducible (10). One hundred and two FFPE samples yielded enough protein to perform the MS analyses (typically, more than 0.5 mg of total protein was recovered from each sample).…”
Section: Protein Extraction and Ms Analysismentioning
confidence: 99%
“…Proteins were extracted from FFPE samples as previously described (10). Briefly, FFPE sections were deparaffinized in xylene and washed twice with absolute ethanol.…”
Section: Total Protein Preparationmentioning
confidence: 99%
“…In addition, protein detection is probably also more reflective of the tumor microenvironment. Several proteomic studies have been conducted on TNBC (3)(4)(5), but no proteomic study was conducted on large cohorts including the clinical outcome of the patients, except a recent comparative proteome analysis that identified a 11-protein signature for aggressive TNBC in a large cohort of 93 microdissected tumors (6). Although microdissection was necessary to elucidate the contribution of TNBC cells, it did not reflect the tumor with its microenvironment that is increasingly described as fundamental to explain the tumor outcome.…”
mentioning
confidence: 99%